Ultrasound with laparoscopy for the diagnosis of abdominal disorders in cattle - Silva, José Ricardo B. [UNESP]; Afonso, José Augusto B.; Mendonça, Carla L.; Cajueiro, Jobson Filipe P.; Alonso, Juliana M. [UNESP]; Alcântara, Uila A.a.; Rebouças, Rodolpho A.; Rodrigues, Celso Antônio [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2021)
This study aimed to evaluate laparoscopy with abdominal ultrasound exams to establish accurate diagnosis and prognosis. The experimental design was a prospective clinical study. Nine adult crossbred bovines suffering from abdominal disorders were admitted to the cattle clinic for clinical examinations. Abdominal ultrasound was carried out, and complete blood counts were performed. Subsequently, exploratory laparoscopy was performed. After surgery (exploratory laparoscopy on the right or left side), animals with a severe prognosis or untreatable clinical condition were euthanised and necropsied. During laparoscopy, circumscribed reticuloperitonitis could not be detected, nor could other abnormalities in the cranioventral region of the abdomen previously observed on ultrasound and confirmed during necropsy. However, alterations due to peritoneal damage, such as adhesions, were observed dorsally in addition to alterations in macroscopic aspects of the peritoneal fluid. Exploratory standing laparoscopy through the paralumbar fossae may constitute a supplementary procedure for diagnosing abdominal disorders in cattle, but it is not suitable in cases of diseases characterised by focal lesions concentrated in the cranioventral region of the abdomen. When associated with clinical, laboratory, and ultrasound examinations, this technique may improve the accurate diagnosis and prognosis of abdominal disorders in cattle.

Este estudo teve como objetivo avaliar a laparoscopia com exames de ultrassom abdominal para estabelecer um diagnóstico e prognóstico precisos. O desenho experimental foi um estudo clínico prospectivo. Nove bovinos adultos mestiços com distúrbios abdominais foram utilizados. Os bovinos admitidos na Clínica de Bovinos foram submetidos a exame clínico, adicionalmente foram realizadas hemograma e ultrassonografia abdominal. Posteriormente, foi realizada laparoscopia exploratória. Após a cirurgia (laparoscopia exploratória no lado direito ou esquerdo), nove animais com manifestações clínicas graves e intratáveis foram sacrificados e necropsiados. Durante a laparoscopia, não foi possível detectar reticuloperitonite circunscrita, bem como outras anormalidades na região crânio-ventral do abdome, previamente observadas na ultrassonografia e confirmadas durante a necropsia. No entanto, alterações devido a dano peritoneal, como aderências, foram observadas dorsalmente. É possível que a laparoscopia exploratória em apoio quadrupedal através da fossa paralombar constitua um procedimento complementar para o diagnóstico de distúrbios abdominais em bovinos, embora não seja adequado em casos de doenças caracterizadas por lesões focais concentradas na região cranioventral do abdome. Quando associada a exames clínicos, laboratoriais e de ultrassom, essa técnica pode melhorar o diagnóstico e prognóstico preciso dos distúrbios abdominais em bovinos.
Estudo da ultrassonografia e laparoscopia para diagnóstico das desordens abdominais em bovinos
Keywords: Ultrasound; laparoscopy; diagnosis; abdominal disorders; cattle; bovine; digestive diseases; reticuloperitonitis; ultrasonography; Ultrassonografia; laparoscopia; diagnóstico; desordens abdominais; bovinos; doenças digestivas; reticuloperitonite